Development and spread of health literacy eLearning: A partnership across Scotland and England. (29th July 2022) - Carlyle, Ruth; Thain, Annette; James, Sally
Abstract: With international health challenges, there are opportunities for collaboration between nations on health issues, including developing and sharing resources for teaching and learning. This article outlines collaboration across Scotland and England to develop a core resource for eLearning on health literacy. It describes the development of the resource with case studies of the implementation in Scotland and England, demonstrating the balance between shared development and tailored implementation. The eLearning was developed to increase awareness of NHS workforce and community partners, supplemented by training for NHS librarians and public health specialists to enable them to provide more tailored training on health literacy techniques.